Efficient Light-Driven Hydrogen Evolution Using a Thiosemicarbazone-Nickel (II) Complex - Panagiotakis, Stylianos; Landrou, Georgios; Nikolaou, Vasilis; Putri, Anisa; Hardré, Renaud; Massin, Julien; Charalambidis, Georgios; Coutsolelos, Athanassios G.; Orio, Maylis (Frontiers in Chemistry, 2019)
In the following work, we carried out a systematic study investigating the behavior of a thiosemicarbazone-nickel (II) complex (NiTSC-OMe) as a molecular catalyst for photo-induced hydrogen production. A comprehensive comparison regarding the combination of three different chromophores with this catalyst has been performed, using [Ir(ppy)2(bpy)]PF6, [Ru(bpy)3]Cl2 and [ZnTMePy]PCl4 as photosensitizers. Thorough evaluation of the parameters affecting the hydrogen evolution experiments (i.e. concentration, pH, solvent nature and ratio), has been performed in order to probe the most efficient photocatalytic system, which was comprised by NiTSC-OMe and [Ir(ppy)2(bpy)]PF6 as catalyst and chromophore, respectively. The electrochemical together with the photophysical investigation clarified the properties of this photocatalytic system and allowed us to propose a possible reaction mechanism for hydrogen production.